2018
DOI: 10.1002/jum.14701
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Needle‐Guidance Technology in Ultrasound‐Guided Percutaneous Procedures Performed by Radiology Residents: A Comparison of Freehand, In‐Plane, Fixed‐Angle, and Electromagnetic Needle Tracking Techniques

Abstract: Radiology resident procedure time and procedure accuracy (as judged by number of pullbacks) are significantly improved by the use IPFA and ENT guidance technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
2
0
2
Order By: Relevance
“…In line with the ease provided by GPS-based route/traffic planning in daily life, insight into the ideal route could also improve needle placement. An assumption that relates to statements made by England et al [ 39 ]. We, however, observed that virtual needle-navigation reduced the needle movement fluency for both groups (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the ease provided by GPS-based route/traffic planning in daily life, insight into the ideal route could also improve needle placement. An assumption that relates to statements made by England et al [ 39 ]. We, however, observed that virtual needle-navigation reduced the needle movement fluency for both groups (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…바늘을 살짝 앞뒤로 반복적으로 움직여 보면(pump maneuver) 바늘 끝을 찾는데 도움이 된다. 또한 탐촉자에 끼우는 유도용 장비를 사용하면 시술 시간이 줄고 바늘을 조정하는 횟수를 감소시켜 특히 비숙련자들에게 도움이 될 수 있다고 알려져 있다( 23 24 ).…”
Section: 기술적 고려 사항unclassified
“…Apart from urology its current use can be traced in thoracic surgery [22], neurosurgery [23], ENT [24] and general surgery [25]. It is described to facilitate the training process of specialists [26] and aid in the diagnosis and treatment of different pathologies [22,23,25,27].…”
Section: The Use Of Electromagnetic-guidance In Medicinementioning
confidence: 99%